Multifunctional gel electrolyte for prolonging service life of AGM lead-acid battery and gelation method

By using multifunctional colloidal electrolyte in AGM batteries to form a porous gel structure, the problem of water loss in lead-acid batteries in high temperature environments is solved, which extends the battery life and improves market competitiveness.

CN119542566APending Publication Date: 2025-02-28CAMEL GRP XIANGYANG BATTERY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411542666.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Water electrolysis and self-discharge will occur during charging, discharge or placement of lead-acid batteries, especially in high-temperature environments, which will cause the battery to lose water, reduce saturation, low-temperature capacity attenuation, and intensify the corrosion of the grid, which seriously affects the service life of the battery.

Method used

A multifunctional colloidal electrolyte and its gel method are provided. By adding colloidal electrolyte to the AGM battery, a colloid layer is formed with a thickness of 5-10mm. The colloid gels into a porous colloid inside the battery, which can adsorb a large amount of electrolyte, replenish the moisture inside the battery, and reduce moisture loss.

Benefits of technology

It extends the service life of AGM batteries, improves the high-temperature cycle life of the battery, reduces moisture loss, and enhances the market competitiveness of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a multifunctional gel electrolyte for prolonging the service life of an AGM lead-acid battery and a gelation method. Belongs to the technical field of lead-acid storage batteries. The invention mainly solves the problem that the existing lead-acid storage battery is easy to lose water due to water electrolysis, self-discharge and the like in the charge-discharge or placement process. The gel electrolyte is mainly characterized by being prepared by mixing sulfuric acid, water glass, a powder additive and a stabilizer, the gelation method comprises the following steps: glue filling: after formation of the AGM battery is finished, adding a gel electrolyte to cover the surface of a cluster for 5-10mm; and gelling: leveling and covering the whole cluster surface when the battery flows along with the roller way by virtue of self fluidity, and gelling into a porous colloid in the battery. A large amount of electrolyte can be adsorbed in the colloid, the storage amount of the electrolyte available for the battery can be increased, water can be supplemented in time when the battery loses water, water loss is reduced, and the water retention agent is mainly used for water retention and water loss reduction of the AGM battery, so that the service life of the AGM battery is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lead-acid batteries, and in particular relates to a multifunctional colloidal electrolyte for improving the service life of an AGM lead-acid battery and a gelling method thereof. Background Art

[0002] During the charging, discharging or storage process, lead-acid batteries will undergo side reactions such as water electrolysis and self-discharge. In addition, when a car is used outdoors under high temperature conditions, the temperature of the lead-acid battery will be higher, which is more likely to cause the battery to lose water. When the water loss reaches a certain level, the battery saturation will decrease, the battery capacity will decay at low temperature, and the grid corrosion will intensify, eventually leading to battery failure and seriously affecting the battery life. Especially for car starter batteries that are in floating charge conditions for a long time, the high temperature environment accelerates the loss of water.

[0003] Therefore, retaining water and reducing water loss can effectively extend the service life of AGM batteries. From this perspective, the present invention provides a gel electrolyte that can absorb a large amount of electrolyte and a gel implementation process thereof, and reduces water loss inside the battery through a material that can provide water to the inside of the battery or reduce water loss to extend the battery's service life, further improving the comprehensive market competitiveness of lead-acid battery products. Summary of the invention

[0004] The purpose of the present invention is to provide a multifunctional colloidal electrolyte and a gelling method thereof for improving the life of AGM lead-acid batteries in view of the above-mentioned deficiencies. By adding the colloidal electrolyte to the formed AGM battery, a 5-10 mm thick colloidal layer can be formed on the surface of the cluster. The colloidal layer gels into a porous colloidal structure inside the battery. A large amount of electrolyte can be adsorbed inside the porous gel structure to increase the storage capacity of the available electrolyte in the battery. When the battery loses water, it can be replenished in time. The porous channels can reduce water loss.

[0005] The technical solution of the colloidal electrolyte of the present invention is: a multifunctional gel for improving the life of AGM lead-acid batteries, characterized in that: the colloidal electrolyte is prepared by mixing sulfuric acid, water glass, powder additives and stabilizers.

[0006] The specific gravity of the sulfuric acid in the technical solution of the colloidal electrolyte of the present invention is 1.37-1.44, and the mass fraction is 80-90 parts; the solid content of the water glass is 40%, and the mass fraction is 10-20 parts; the mass fractions of the sulfuric acid and the water glass are 100 parts in total.

[0007] The powder additive in the technical solution of the colloidal electrolyte of the present invention consists of aluminum silicate and hollow glass powder, and the ratio thereof is 1:1.

[0008] The specific gravity of the sulfuric acid in the technical solution of the colloidal electrolyte of the present invention is 1.37-1.44, and the mass fraction is 80-90 parts; the solid content of the water glass is 40%, and the mass fraction is 10-20 parts; the mass fractions of the sulfuric acid and the water glass are 100 parts in total; and the mass fraction of the powder additive is 0.5-2 parts.

[0009] The stabilizer in the technical solution of the colloidal electrolyte of the present invention is composed of one or more of polyvinyl pyrrolidone, polyacrylamide and polyvinyl alcohol.

[0010] In the technical solution of the colloidal electrolyte of the present invention, the sulfuric acid is a sulfuric acid solution with a density of 1.37-1.44 prepared by adding pure water with a conductivity of ≤10us / cm to analytical pure sulfuric acid, and the mass portion is 80-90 parts; the water glass is sodium silicate with a solid content of 40%, and the mass portion is 10-20 parts; the mass portions of the sulfuric acid and the water glass are 100 parts in total; the powder additive is composed of aluminum silicate and hollow glass powder, and the ratio is 1:1, and the mass portion is 0.5-2 parts; the mass portion of the stabilizer is 0.05-0.5 parts.

[0011] In the technical solution of the gel solution of the present invention, the weight portion of the powder additive is 0.8-1.6 parts; the weight portion of the stabilizer is 0.2-0.35 parts.

[0012] In the technical solution of the gel solution of the present invention, the weight portion of the powder additive is 0.5-0.8 parts; the weight portion of the stabilizer is 0.05-0.2 or 0.35-0.5 parts.

[0013] In the technical solution of the gel solution of the present invention, the weight portion of the powder additive is 1.6-2 parts; the weight portion of the stabilizer is 0.05-0.2 or 0.35-0.5 parts.

[0014] The technical solution of the gel method of the present invention is: a gel method of a multifunctional colloidal electrolyte for improving the life of an AGM lead-acid battery, characterized in that it comprises the following steps: A. Glue filling: After the AGM battery is formed, let it stand for 2 hours, and then add a set volume of colloidal electrolyte through the acid filling port, so that the colloidal electrolyte can cover the cluster surface with a thickness of 5-10mm; B. Gel: The colloidal electrolyte relies on its own fluidity to flow and cover the entire cluster surface when the battery flows along the roller. As time goes by and the temperature rises, the colloidal electrolyte gels into a porous colloid inside the battery.

[0015] The beneficial effects of the present invention are: The multifunctional colloidal electrolyte of the present invention is prepared by filling the colloidal electrolyte on the AGM battery after formation. After the filling is completed, the colloidal electrolyte quickly spreads over the surface of the cluster under its own flow to form a 5-10mm thick colloidal layer. During the static state of the battery, the colloidal particles condense through siloxanol to form silicon oxygen bonds to build the skeleton structure of the colloidal body. Another part of the smaller particles can form a three-dimensional network in the form of hydrogen bonds through acid-base combination to lock the electrolyte. When the electrolyte in the partition is reduced due to water loss, the electrolyte adsorbed in the colloid can be supplemented, thereby improving the high-temperature cycle life of the battery and further improving the comprehensive market competitiveness of lead-acid battery products.

[0016] The present invention is mainly used for retaining water in AGM batteries, reducing water loss, and thus extending the service life of the AGM batteries. DETAILED DESCRIPTION

[0017] The specific implementation of the present invention is described in detail below.

[0018] The present invention discloses a multifunctional colloidal electrolyte for improving the life of an AGM lead-acid battery, which is a gel solution prepared by mixing sulfuric acid, water glass, a powder additive and a stabilizer. The sulfuric acid is a sulfuric acid solution with a density of 1.37-1.44 prepared by adding pure water with a conductivity of ≤10us / cm to analytical pure sulfuric acid, and the weight portion is 80-90 parts. The water glass is a sodium silicate with a solid content of 40%, and the weight portion is 10-20 parts. The weight portions of sulfuric acid and water glass are 100 parts in total. The powder additive is composed of aluminum silicate and hollow hollow glass powder, and the ratio thereof is 1:1. The weight portion of the powder additive is 0.5-2 parts, which assists in forming more pores in the gelation process of the colloidal electrolyte to ensure the formation of gas channels, increase the skeleton structure of the entire colloidal gel, and reduce the thixotropy of the colloid. The stabilizer is composed of one or more of polyvinyl pyrrolidone, polyacrylamide and polyvinyl alcohol, and the weight portion of the stabilizer is 0.05-0.5 parts. It plays a role in controlling the gel time in the colloidal electrolyte. At the same time, after the formation of the colloid, the alcohol hydroxyl group in the stabilizer can combine with water through hydrogen bonds, effectively reducing water loss. Among them, the weight portion of the powder additive is 0.8-1.6 parts, and the weight portion of the stabilizer is 0.2-0.35 parts; or the weight portion of the powder additive is 0.5-0.8 parts, and the weight portion of the stabilizer is 0.05-0.2 or 0.35-0.5 parts; or the weight portion of the powder additive is 1.6-2 parts, and the weight portion of the stabilizer is 0.05-0.2 or 0.35-0.5 parts.

[0019] The present invention discloses a gel method for a multifunctional colloidal electrolyte for improving the life of an AGM lead-acid battery, comprising the following steps: A. Glue filling: After the AGM battery is formed, let it stand for 2 hours, and then add a set volume of colloidal electrolyte through the acid filling port, so that the colloidal electrolyte can cover the cluster surface with a thickness of 5-10mm; B. Gel: The colloidal electrolyte relies on its own fluidity to flow and cover the entire cluster surface when the battery flows along the roller. As time goes by and the temperature rises, the colloidal electrolyte gels into a porous colloid inside the battery.

[0020] It has multiple functions: ① The colloid has a porous gel structure, which can absorb a large amount of electrolyte inside, increase the storage capacity of the battery's available electrolyte, and can be replenished in time when the battery loses water; ② The porous gel structure of the colloid can ensure the gas recombination channel during the charging process of the AGM battery. At the same time, the existence of the porous channel prolongs the path of water loss and can reduce water loss.

[0021] Example 1 In this embodiment, sulfuric acid is 90 parts, water glass is 10 parts, the powder additive is 1 part by weight, the stabilizer is polyvinyl pyrrolidone, the weight portion is 0.15 parts, the sulfuric acid is analytical pure sulfuric acid, and the density of the sulfuric acid solution is 1.37-1.44 prepared by adding pure water with a conductivity of ≤10us / cm, the water glass is sodium silicate, and the solid content is 40%, and the powder additive is composed of aluminum silicate and hollow glass powder, and the ratio is 1:1. Add the powder additive and stabilizer in the above proportion to sulfuric acid, stir evenly, then place the mixture in a 0°C water bath, stir, slowly add water glass, stir for 30 minutes, to obtain the colloid of the present invention, and store at low temperature for later use.

[0022] Example 2 In this embodiment, sulfuric acid is 80 parts, water glass is 20 parts, the powder additive is 1.5 parts by weight, the stabilizer is polyvinyl pyrrolidone, the weight portion is 0.45 parts, the sulfuric acid is analytical pure sulfuric acid, and the density of the sulfuric acid solution is 1.37-1.44 prepared by adding pure water with a conductivity of ≤10us / cm, the water glass is sodium silicate, and the solid content is 40%, and the powder additive is composed of aluminum silicate and hollow glass powder, and the ratio is 1:1. Add the powder additive and stabilizer in the above proportion to sulfuric acid, stir evenly, then place the mixture in a 0°C water bath, stir, slowly add water glass, stir for 30 minutes, to obtain the colloid of the present invention, and store at low temperature for later use.

[0023] Example 3 In this embodiment, sulfuric acid is 90 parts, water glass is 10 parts, powder additive is 0.5 parts by weight, stabilizer is 0.1 parts by weight of polyacrylamide and 0.1 parts by weight of polyvinyl alcohol, sulfuric acid is analytical pure sulfuric acid, and a sulfuric acid solution with a density of 1.37-1.44 is prepared by adding pure water with a conductivity of ≤10us / cm, water glass is sodium silicate, and the solid content is 40%, and the powder additive is composed of aluminum silicate and hollow glass powder, and the ratio is 1:1. Add the powder additive and stabilizer in the above proportion to sulfuric acid, stir evenly, then place the mixture in a 0°C water bath, stir, slowly add water glass, stir for 30 minutes, to obtain the colloid of the present invention, and store at low temperature for later use.

[0024] Example 4 In this embodiment, sulfuric acid is 85 parts, water glass is 15 parts, powder additive is 2 parts by weight, stabilizer is polyacrylamide with a weight part of 0.15 parts, polyvinyl alcohol with a weight part of 0.15 parts, sulfuric acid is analytical pure sulfuric acid, and a sulfuric acid solution with a density of 1.37-1.44 is prepared by adding pure water with a conductivity of ≤10us / cm, water glass is sodium silicate, and the solid content is 40%, and the powder additive is composed of aluminum silicate and hollow glass powder, and the ratio is 1:1. Add the powder additive and stabilizer in the above proportion to sulfuric acid, stir evenly, then place the mixture in a 0°C water bath, stir, slowly add water glass, stir for 30 minutes, to obtain the colloid of the present invention, and store at low temperature for later use.

[0025] The colloidal electrolytes of the above four embodiments were respectively poured into AGM 40Ah experimental batteries for testing, and the capacity and water consumption tests were performed according to GB / T5008, and the J2801 test was performed according to the SAE standard.

[0026] The test results of the battery added with the colloidal electrolyte prepared in Examples 1-4 are as follows: In summary, in the embodiments described in the present invention, the addition of colloidal electrolyte is adopted, and the C20 capacity is 41.25Ah, 42.58Ah, 43.57 Ah, and 42.21 Ah, respectively, and the corresponding water consumption is 1.02g / Ah, 1.35g / Ah, 1.22g / Ah, and 1.53g / Ah, respectively, and the corresponding J2801 life is 10 units, 9 units, 10 units, and 9 units, respectively, indicating that the addition of the colloidal electrolyte improves the battery capacity, water consumption, and 2801 life. The presence of sulfuric acid electrolyte in the colloidal electrolyte can increase the battery capacity; the presence of hydroxyl structure in the porous gel can form hydrogen bonds to lock water, and the porous channels extend the water loss path and reduce the water consumption of the battery; the electrolyte in the gel can be slowly released into the battery during the high temperature life of 2801, delaying the corrosion growth and failure of the grid caused by the lack of electrolyte, thereby achieving the effect of extending the battery life.

Claims

1. A multifunctional colloidal electrolyte for improving the life of AGM lead-acid batteries, characterized by: A colloidal electrolyte made by mixing sulfuric acid, water glass, powder additives and stabilizers.

2. The multifunctional colloidal electrolyte for improving the life of an AGM lead-acid battery according to claim 1, characterized in that: The specific gravity of the sulfuric acid is 1.37-1.44, and the mass fraction is 80-90 parts; the solid content of the water glass is 40%, and the mass fraction is 10-20 parts; the mass fractions of the sulfuric acid and the water glass in total are 100 parts.

3. The multifunctional colloidal electrolyte for improving the life of AGM lead-acid batteries according to claim 1, characterized in that: The powder additive consists of aluminum silicate and hollow glass powder in a ratio of 1:

1.

4. The multifunctional colloidal electrolyte for improving the life of an AGM lead-acid battery according to claim 3, characterized in that: The specific gravity of the sulfuric acid is 1.37-1.44, and the mass fraction is 80-90 parts; the solid content of the water glass is 40%, and the mass fraction is 10-20 parts; the mass fractions of the sulfuric acid and the water glass are 100 parts in total; and the mass fraction of the powder additive is 0.5-2 parts.

5. The multifunctional colloidal electrolyte for improving the life of an AGM lead-acid battery according to claim 1, characterized in that: The stabilizer is composed of one or more of polyvinyl pyrrolidone, polyacrylamide and polyvinyl alcohol.

6. The multifunctional colloidal electrolyte for improving the life of an AGM lead-acid battery according to claim 5, characterized in that: The sulfuric acid is prepared by adding pure water with an electrical conductivity of ≤10us / cm to analytical pure sulfuric acid to form a sulfuric acid solution with a density of 1.37-1.44, with a mass fraction of 80-90 parts; the water glass is sodium silicate with a solid content of 40%, with a mass fraction of 10-20 parts; the mass fractions of the sulfuric acid and the water glass are 100 parts in total; the powder additive is composed of aluminum silicate and hollow glass powder, with a ratio of 1:1 and a mass fraction of 0.5-2 parts; the mass fraction of the stabilizer is 0.05-0.5 parts.

7. The multifunctional colloidal electrolyte for improving the life of an AGM lead-acid battery according to claim 6, characterized in that: The mass proportion of the powder additive is 0.8-1.6 parts; the mass proportion of the stabilizer is 0.2-0.35 parts.

8. The multifunctional colloidal electrolyte for improving the life of an AGM lead-acid battery according to claim 6, characterized in that: The mass proportion of the powder additive is 0.5-0.8 parts; the mass proportion of the stabilizer is 0.05-0.2 or 0.35-0.5 parts.

9. The multifunctional colloidal electrolyte for improving the life of an AGM lead-acid battery according to claim 6, characterized in that: The mass fraction of the powder additive is 1.6-2 parts; the mass fraction of the stabilizer is 0.05-0.2 or 0.35-0.5 parts.

10. A gelling method using a multifunctional colloidal electrolyte for improving the life of an AGM lead-acid battery according to any one of claims 1 to 9, characterized in that: The following steps are involved: A. Glue filling: After the AGM battery is formed, let it stand for 2 hours, and then add a set volume of colloidal electrolyte through the acid filling port, so that the colloidal electrolyte can cover the cluster surface with a thickness of 5-10mm; B. Gel: The colloidal electrolyte relies on its own fluidity to flow and cover the entire cluster surface when the battery flows along the roller. As time goes by and the temperature rises, the colloidal electrolyte gels into a porous colloid inside the battery.